2020
DOI: 10.2340/00015555-3399
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XVII Processing and Blistering Skin Diseases

Abstract: SIGNIFICANCECollagen XVII (COL17, also known as BP180) is an im portant molecule, which maintains stable adhesion between the dermis and epidermis. Genetic and acquired dysfunc tions of COL17 lead to blistering skin diseases. However, the expression of COL17 is tightly regulated, depending on various settings, including woundhealing, proliferation and differentiation. Dysregulation of COL17 processing may be associated with the development of blistering skin di seases; thus, it is important to understand the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…It is not fully understood why in LABD the 120 and 97 kDa fragments of BP180 are targeted by IgA rather than IgG autoantibodies (11,12). Also, BP patients have IgA autoantibodies that recognize the aminoterminal epitopes of the BP180 ectodomain particularly strongly (39).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is not fully understood why in LABD the 120 and 97 kDa fragments of BP180 are targeted by IgA rather than IgG autoantibodies (11,12). Also, BP patients have IgA autoantibodies that recognize the aminoterminal epitopes of the BP180 ectodomain particularly strongly (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports that LABD IgA autoantibodies target the shed ectodomain and 97 kDa fragment of BP180 particularly strongly (11,19,20) prompted us to investigate whether plasmin digestion of BP180 would produce neoepitopes that would be recognized by IgA autoantibodies in samples from DH (n = 20), CD (n = 20), and BP (n = 20) patients and healthy controls (n = 22). After partial plasmin digestion, the remaining undigested full-length BP180 was recognized by 5% of DH samples, 10% of both CD and BP samples and 13.6% of control samples ( Figure 2B, Table 1).…”
Section: Immunoblotting Analyses Of Autoantibodies Against Bp180mentioning
confidence: 99%
See 2 more Smart Citations
“…Cleavage of basement membrane components can directly damage the integrity and function of the dermal-epidermal junction, promoting epidermal shedding and blistering, thus causing the development of autoimmune blistering diseases. 92,93 Furthermore, Matsubara et al have revealed that exogenous GZMB induces the cleavage of retinal pigment epithelial-derived tight junctional and ECM proteins, and exacerbates ECM remodelling in Bruch's membrane and degradation of the blood-retina barrier, which is considered an early signal event for the development of age-related macular degeneration (a multifactorial, chronic inflammatory eye disease). 16 Turner et al have confirmed that GZMB contributes to barrier dysfunction in oxazoloneinduced skin inflammation through E-cadherin and filaggrin cleavage.…”
Section: Gzmb and Elimination Of Viruses Or Virus-infected Cellsmentioning
confidence: 99%